A city's "urban crack" at 4 a.m.: A case study of morning market vendors in Beijing's Longfu Temple area. (January 2018) - Li, Jianing; Ren, Longyun; Hu, Tianhui; Wang, Fang
Abstract: Generally found in the old city, "urban crack" refers to a narrow area that is hidden behind a prosperous area and was once flourished but no longer full of energy. Street vendors often regard "urban crack" areas as their main working places because they are from lower socioeconomic groups. However, these vendors occupy cities' marginal spaces during unconventional times, which is a strategy of agency. Choosing the Longfu Temple morning market, a street market in old Beijing city as the study area, this study focused on how the vendors successfully conducted their business in the morning market, which is a type of "urban crack". Inspired by Cresswell's framework (2010) of the six facets of mobility, the paper constructed a framework for agency to explain street vendors' activities, which includes the following six aspects: motive force, route, speed, rhythm, experience, and friction. Relying on the perspective of time and space, this study revealed that disadvantaged groups represented by morning market vendors are flexible and vigorous. By incorporating agency, these vendors' tactics consider time and space in order to support their way of life. Focusing on street vendors is not a unique case to develop the concept of "urban crack", this study makes an original contribution to provide a research reference for other countries that are faced with similar social realities. Highlights: "Urban crack" is often ignored by the authorities and suitable for street markets. Morning market represents an unconventional use of city space. Agency's six facets are used to explain the morning market vendors' activities. Vendors occupy marginal spaces during unconventional times and are full of agency.